First record of the hermit crab genus Cestopagurus Bouvier, 1897 (Crustacea: Decapoda: Anomura: Paguridae) from the South Pacific Ocean and description of a new species - Komai, Tomoyuki; Tsuchida, Shinji; Clark, Malcolm R. (Zootaxa, 2014)
A fifth species of the pagurid genus Cestopagurus Bouvier, 1897, is described and illustrated on the basis of a single male specimen collected at a depth of 499 m from Hinepuia submarine volcano in the Kermadec Arc, New Zealand. The new species, C. hinepuia, appears similar to C. puniceus Komai & Takeda, 2005 known from waters off Japan, but the different armature of chelipeds distinguishes the new species. It is the first representative of the genus recorded from the South Pacific Ocean. A key for identification of species of the genus is presented.